Safety and efficacy of rituximab as first- and second line treatment in multiple sclerosis – A cohort study. Issue 1 (January 2021) - Torgauten, Hilde Marie; Myhr, Kjell-Morten; Wergeland, Stig; Bø, Lars; Aarseth, Jan H; Torkildsen, Øivind
Background: Rituximab is increasingly used as off-label therapy in multiple sclerosis (MS). More data are needed on safety and efficacy of rituximab, particularly in cohorts of de novo patients and patients in early therapy escalation. Objective: To investigate the safety and efficacy of off-label treatment with rituximab in an MS-cohort of predominantly de novo patients or as therapy escalation. Methods: We retrieved safety and efficacy data from the Norwegian MS-registry and biobank for all MS-patients treated with rituximab at Haukeland University Hospital, Bergen, Norway, during a four year period. Results: In the 365 MS-patients (320 relapsing-remitting MS (RRMS), 23 secondary progressive MS (SPMS), and 22 primary progressive MS (PPMS)), the overall annualized relapse rate (ARR) was 0.03 and annualized drug discontinuation rate (ADDR) was 0.05. NEDA-3 was achived in 79% of patients with available data (n=351). Sixty-one patients experienced infusion-related adverse events of which two were serious (CTCAE grade 3–4). Eighteen patients experienced serious non-infusion related adverse events, of which 16 were infections. Infections (n = 34; 9.3%, CTCAE grade 2-5), hypogammaglobulinemia (n = 19, 5.2%) and neutropenia (n = 16; 4.4%) were the most common non-infusion-related adverse events. Conclusion: Rituximab was a safe and highly efficient disease modifying therapy in this cohort of MS-patients; however, infections and neutropenia need to be monitored.